The Relationship between Mathematics Score and Mathematics Anxiety among Biology Education Students - Benidiktus Tanujaya; Jeinne Mumu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Students need to be anxiety-free when it comes to mathematics. This phenomenon is an unpleasant sensation that interferes with someone's ability to communicate well with mathematics. Although several studies have investigated the relationship between mathematics anxiety and mathematics proficiency, none have explored the effect of mathematics anxiety on individual students' mathematics scores, particularly in biology education students. A correlational analysis was performed with quantitative research methods to explore the association between mathematics scores and mathematics anxiety. 68 participants were recruited for the study, using non-probability sampling, voluntarily and purposively. A student's mathematics anxiety was assessed using a mathematical anxiety scale. The data were analyzed by correlation and regression analysis to determine whether mathematics anxiety was associated with student success. The mathematical model is the best approximation of the relationship between variables described by the equation (3.6 + 0.0 A1 - 0.5 A2 - 1.6 A3 - 2.3 A4 - 2.9 A5). The results suggest that poor mathematics skills increase with levels of anxiety. Students with the least amount of anxiety are predicted to get passing grades of A and B, whereas those with more anxiety are likely to get lower grades of D and E.